Legal Studies Regarding Pornography On Live Streaming Through Social Media In The Era Of Digital Disruption - Tanaya, Farra Shalma; Rompis, Adrian E.; Rafianti, Laina (JURNAL LEGALITAS, 2022)
Technology in human life lately is increasingly needed and continues to develop. One form of development that occurs is the emergence of the Live Streaming feature. This feature appears on various social media platforms. There are even new applications that are intended to do Live Broadcasting—unfortunately, not only positive things that emerged due to this development. There have been several cybercrimes (cyber laws) that have negatively influenced internet users. Among them is the emergence of internet pornography. There is much Live Streaming that contains pornography in Live Broadcasting applications. The approach method used in this research is normative juridical, by examining the literature and reviewing positive law, which relates to the Law of Technology, Information and Electronic Transactions, and the Law of Pornography. This research will study the most appropriate way to regulate how Live Streaming containing pornography is viewed from Law Number 11 of 2008 jo. Law Number 19 of 2016 concerning Information and Electronic Transactions (ITE act) and Law Number 44 of 2008 concerning Pornography (Pornography act) and actions that the Government can take to minimize pornographic content on Live Streaming on social media in Indonesia.